PENGARUH PENGGUNAAN GADGET DAN LINGKUNGAN BELAJAR TERHADAP MINAT BELAJAR IPS SISWA KELAS VII SEMESTER GENAP DI SMP NEGERI 1 KAPONGAN SITUBONDO TAHUN PELAJARAN 2017/2018 - Irma Noervadila; Nur Laila (STKIP PGRI SITUBONDO, 2018)
Teaching and learning is the main activity in school. The hope that never disappears from a teacher is that students succeed in learning. This success is always accompanied by efforts both from the teacher and from the students themselves. Based on observations carried out at SMP Negeri 1 Kapongan Situbondo, there were several problems, one of which was the low student interest in learning. The data shows that 14 students in class VII-A and 13 students in class VII-B have low interest in learning and are starting to be interested in other activities. Students are more interested in playing gadgets and talking to friends next door without paying attention to the teacher's explanation. This study is an ex-post facto study because it only reveals data about events that have taken place on respondents who have no treatment and control. Based on the Pie Chart of the tendency of learning interest variables, it was shown that the seventh grade students of SMP Negeri 1 Kapongan who had a very high category of interest in learning were 2 students (4.88%), the high category was 11 students (26.83%), the low category was 22 students (53.66%) and the very low category was 6 students (14.63%). Student interest is low because there are still many students who have not met the indicator of interest in learning, namely the indicator of interest in what is being learned. The results of the prerequisite analysis and hypothesis testing showed that there was an effect of using gadgets and the learning environment together on learning interest by 42.1% with a significance value of 0.000.